2002
DOI: 10.1002/hep.1840360615
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of autoimmune hepatitis to primary sclerosing cholangitis: A sequential syndrome

Abstract: Recently, the autoimmune hepatitis (AIH)/primary sclerosing cholangitis (PSC) overlap syndrome has been reported increasingly. In this syndrome, patients present with features of both AIH and PSC. It has been suggested that the 2 diseases may be sequential in their occurrence, whereby patients have features of AIH and then after a number of years develop features of PSC, but clear confirmation of evolution has not been documented in adults. We describe 6 adult cases in which PSC was diagnosed many years after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 24 publications
1
34
0
2
Order By: Relevance
“…Interestingly, all patients with overlap syndromes AIH‐PSC had multiple risk factors for recurrence, as prior studies have shown that inflammatory bowel disease , recurrent acute cellular rejection (ACR) and intact colon to be risk factors for PSC recurrence. In this study, patients with overlap syndromes AIH‐PSC had ulcerative colitis and intact colon, and each experienced at least one episode of ACR, which may explain the high frequency of recurrence in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, all patients with overlap syndromes AIH‐PSC had multiple risk factors for recurrence, as prior studies have shown that inflammatory bowel disease , recurrent acute cellular rejection (ACR) and intact colon to be risk factors for PSC recurrence. In this study, patients with overlap syndromes AIH‐PSC had ulcerative colitis and intact colon, and each experienced at least one episode of ACR, which may explain the high frequency of recurrence in this subgroup of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, when the revised International Autoimmune Hepatitis Group (IAIHG) criteria are used, between 2 and 19% of patients with PBC have overlap syndromes . Similarly, 7 to 14% of patients with PSC meet the criteria for overlap syndromes when the revised IAIHG criteria are employed , and these patients also tend to have a worse prognosis .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of AIH appears to be higher in children with PSC 305 306. PSC may develop many years after a diagnosis of AIH 307. The prevalence of large duct PSC in adults with AIH has recently been reported as 2% and 10% based on magnetic resonance cholangiopancreatography (MRCP) surveys 77 78.…”
Section: G Specific Clinical Problemsmentioning
confidence: 99%
“…This disorder is well described in patients with IBD especially UC [39]. There is published data that shows patients with IBD and AIH who subsequently go on to develop PSC [38, 40, 41]. The significance of this relationship with IBD is still unclear, and the onset of disease can occur at anytime before or after the diagnosis of IBD.…”
Section: Primary Sclerosing Cholangitis/autoimmune Hepatitis (Psc/mentioning
confidence: 99%